Answer:
see explanation
Explanation:
(a)
Given
= x + 7
Multiply both sides by 2
4x - 1 = 2(x + 7) ← distribute
4x - 1 = 2x + 14 ( subtract 2x from both sides )
2x - 1 = 14 ( add 1 to both sides )
2x = 15 ( divide both sides by 2 )
x =
= 7.5
(b)
Given
3x + 2 =
![(2x+13)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sed87zrmcehio6cr7f3fr45rwl4squlkqx.png)
Multiply both sides by 3
3(3x + 2) = 2x + 13 ← distribute left side
9x + 6 = 2x + 13 ( subtract 2x from both sides )
7x + 6 = 13 ( subtract 6 from both sides )
7x = 7 ( divide both sides by 7 )
x = 1